Multi-substituted garnet-type electrolytes for solid-state lithium batteries. Issue 4 (March 2020) - Song, Shufeng; Wu, Yongmin; Dong, Zhencai; Deng, Fan; Tang, Weiping; Yao, Jianyao; Wen, Zhaoyin; Lu, Li; Hu, Ning; Molenda, Janina
Abstract: Lithium garnets are considered as advanced solid electrolytes for safe and high-energy-density solid-state lithium batteries. A multi-substituted strategy illustrating in this work is substitution of Li by Ga and Zr by Ta/Ba, therefore stabilizing and densifying the cubic lithium garnets thus improving the ionic conductivities. The influence of Ga substitution on garnet phase, microstructure and conductivity of Li6.7-3x Gax La3 Zr1.55 Ta0.4 Ba0.05 O12 garnets is systematically studied. The developed multi-substituted garnet-type electrolytes demonstrate high ambient-temperature conductivity of 1.02 × 10 -3 S cm -1 . Moreover, the multi-substituted garnet reveals impressive capability of alleviating lithium metal dendrites over 800 h under current of 0.01 mA cm -2 to 0.5 mA cm -2, promising solid-state battery applications.